2015
DOI: 10.1080/07315724.2014.938182
|View full text |Cite
|
Sign up to set email alerts
|

Eating Disorders and Psychopathological Traits in Obese Preadolescents and Adolescents

Abstract: Findings from our study demonstrate that in preadolescence and adolescence, obesity is significantly associated to some traits typical of ED and to psychological problems in general. Although no inference can be made with regard to direction of causality, it is possible to conclude that overweight preadolescents and adolescents can be prone to display problematic traits more commonly associated to eating disorders and to present a high degree of mental distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…tive behaviors experienced by the children and adolescents, their body dissatisfaction and with intentional or deliberate damage to their bodies. These results are consistent with other studies reported in the literature[20] [21]. The results propose that there may be a group of children and adolescents vulnerable to the development of "extreme" behaviors of high risk for health, such as drunkenness, the use of marijuana, cocaine and glue or cement inhalation to intentionally harm themselves and binge eating.…”
supporting
confidence: 92%
“…tive behaviors experienced by the children and adolescents, their body dissatisfaction and with intentional or deliberate damage to their bodies. These results are consistent with other studies reported in the literature[20] [21]. The results propose that there may be a group of children and adolescents vulnerable to the development of "extreme" behaviors of high risk for health, such as drunkenness, the use of marijuana, cocaine and glue or cement inhalation to intentionally harm themselves and binge eating.…”
supporting
confidence: 92%
“…The psychological profile of obese patients is often characterized by anxious and depressive symptoms, impulsivity, insecure and poor attachment quality, low self-esteem, and body dissatisfaction ( 7 ). The presence of these psychopathological traits could lead to food consumption as a dysfunctional coping strategy in response to negative emotions, in absence of effective emotion regulation strategies, resulting in development of obesity ( 8 ). During the eligibility evaluation for bariatric surgery, emotion regulation and emotion recognition are seldom assessed, although neurobiological processes concerning self-regulation, including control over eating behaviors, are strongly influenced by emotions ( 9 ).…”
Section: Introductionmentioning
confidence: 99%